Pemodelan Sirkulasi Air Laut Dan Penyebaran Logam Berat Cadmium (Cd) di Kolam Pelabuhan Tanjung Priok - Mutiara R. Putri; Dadang K. Mihardja (Jurnal Matematika & Sains, 1999)
In this study we had been used mathematical model that consist of hydrodynamics and pollutant transport two dimensional depth avaraged models. The driven forces of current that considered in the hydrodynamics model are tidal, monsoon wind, and river discharges. The factors that considered in the waste transport model are advection by current, turbulence diffusion, and load waste sources of cadmium (Cd). The model assumtions are constantly load waste from rivers and persistent waste (chemical reactions and degradation by bioactivities are assumed zero). Simulation results show that in Tanjung Priok harbour the distributions of cadmium follow the current pattern and the consentrations has been over ambient which allowed. The average accuracy of model in this study is about 50 to 60%.